The role of Graphic Design in communicating public messages an extracted study - محەممەد, آ.م.د. کاروان عەبدوڵڵا محەممەد; ئەحمەد, ئارام مەحموود ئەحمەد (Sulaimani Journal for Humanities, 2025)
This research aims to explore the role of graphic design on the effectiveness of public relations messages, with particular emphasis on website design. In today’s digital era, websites have become the quickest and most accessible means of communication, as people increasingly depend on modern technology in their everyday lives.To achieve this, the researcher employed a descriptive methodology complemented by qualitative analysis, utilizing academic sources and examining the websites of three institutions: the University of Sulaimani, Sulaimani Polytechnic University, and Halabja University. The objective was to gather, describe, and analysis data related to graphic design and its influence on the communication of public relations messages.The findings indicate that graphic design is key in this domain. It captures users' attention, encourages extended interaction with the website, and shapes their perceptions of the institution. Effective design also facilitates clearer information sharing, enhancing the overall connection between the institution and its audience.When evaluating the user interface design of university websites, the websites for Sulaimani University, Sulaimani Polytechnic University, and Halabja University exhibit the fewest shortcomings, making them practical for conveying public relations messages. However, there are notable issues regarding user experience. Visitors often struggle to access certain information due to some departments not publishing content or providing incorrect details. Additionally, technical errors within the user interface create barriers for users, leading to frustration and reduced time spent on the site, ultimately hindering the effective delivery of messages.
Keywords: graphic; graphic design; public relation; message; website design